Superconductivity in the High‐Entropy Ceramics Ti0.2Zr0.2Nb0.2Mo0.2Ta0.2Cx with Possible Nontrivial Band Topology - Lingyong Zeng; Xunwu Hu; Yazhou Zhou; Mebrouka Boubeche; Ruixin Guo; Yang Liu; Si‐Chun Luo; Shu Guo; Kuan Li; Peifeng Yu; Chao Zhang; Wei‐Ming Guo; et al. (Advanced Science, 2024)
Abstract Topological superconductors have drawn significant interest from the scientific community due to the accompanying Majorana fermions. Here, the discovery of electronic structure and superconductivity (SC) in high‐entropy ceramics Ti0.2Zr0.2Nb0.2Mo0.2Ta0.2Cx (x = 1 and 0.8) combined with experiments and first‐principles calculations is reported. The Ti0.2Zr0.2Nb0.2Mo0.2Ta0.2Cx high‐entropy ceramics show bulk type‐II SC with Tc ≈ 4.00 K (x = 1) and 2.65 K (x = 0.8), respectively. The specific heat jump (∆C/γTc) is equal to 1.45 (x = 1) and 1.52 (x = 0.8), close to the expected value of 1.43 for the BCS superconductor in the weak coupling limit. The high‐pressure resistance measurements show a robust SC against high physical pressure in Ti0.2Zr0.2Nb0.2Mo0.2Ta0.2C, with a slight Tc variation of 0.3 K within 82.5 GPa. Furthermore, the first‐principles calculations indicate that the Dirac‐like point exists in the electronic band structures of Ti0.2Zr0.2Nb0.2Mo0.2Ta0.2C, which is potentially a topological superconductor. The Dirac‐like point is mainly contributed by the d orbitals of transition metals M and the p orbitals of C. The high‐entropy ceramics provide an excellent platform for the fabrication of novel quantum devices, and the study may spark significant future physics investigations in this intriguing material.